Play the plug: How bacteria modify recognition by host receptors? - Tiruvayipati, Suma; Hameed, Dharjath S.; Ahmed, Niyaz (Frontiers in Microbiology, 2022)
The diverse microbial community that colonizes the gastrointestinal tract has remarkable effects on the host immune system and physiology resulting in homeostasis or disease. In both scenarios, the gut microbiota interacts with their host through ligand-receptor binding whereby the downstream signaling processes determine the outcome of the interaction as disease or the counteractive immune responses of the host. Despite several studies on microbe-host interactions and the mechanisms by which this intricate process happens, a comprehensive and updated inventory of known ligand-receptor interactions and their roles in disease is paramount. The ligands which originate as a result of microbial responses to the host environment contribute to either symbiotic or parasitic relationships. On the other hand, the host receptors counteract the ligand actions by mounting a neutral or an innate response. The varying degrees of polymorphic changes in the host receptors contribute to specificity of interaction with the microbial ligands. Additionally, pathogenic microbes manipulate host receptors with endogenous enzymes belonging to the effector protein family. This review focuses on the diversity and similarity in the gut microbiome-host interactions both in health and disease conditions. It thus establishes an overview that can help identify potential therapeutic targets in response to critically soaring antimicrobial resistance as juxtaposed to tardy antibiotic development research.